Hubungan Dukungan Suami Dengan Pencapaian Peran Ibu (Pendekatan Teori Ramona T. Mercer) Pada Ibu Primipara di Ruang Mawar RSI Jemursari Surabaya - Raden Khairiyatul Afiyah; Ratna Yunita Sari; Imamatul Faizah (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
Husband’s support is a supporting factor of success in achieving the role of mother.Up to now, many husbands found in the society pay low attention and do not accompany their wives since early pregnancy until childbirth process. The purpose of this study was to find out the correlation between the husband’s support and the achievement of primipara mother’s roles hospitalized in Mawar room - RSI Jemursari Surabaya. This analytic study using cross sectional designinvolved the population of primipara mothers hospitalized in Mawar room - RSI Jemursari Surabaya, totaling 50 mothers. The samples of 44 respondents were collected using consecutive sampling technique. The independent variable was the husband’s support, whereas the dependent variable was the achievement of primipara mother’s roles. Questionnaires were used to collect the data analyzed using Mann-Whitney test with the level of significance α = 0.05. The result of study showed that nearly all of the 44 respondents (86.4%) received good husband’s support, whereas nearly all (90.9%) achieved their roles. Moreover, the result of Mann-Whitney test showed that p = 0.000 and the level of significance α = 0.05 so that H0 was rejected because P < 0.05 so that there was a correlation between the husband’s support and the achievement of primipara mother’s roles hospitalized in Mawar room - RSI Jemursari Surabaya. In conclusion, the bigger the husbands gave their supports, the easier the mothers achieved their roles.